PENGARUH MARKETING MIX TERHADAP PENJUALAN PADA TOKO KARPET AB07 YOGYAKARTA - Anis Futihatu Rohmah; Beta Asteria (Program Studi Manajemen Fakultas Ekonomi UST, 2023)
The objective of this study was to determine how the carpet shop AB07 Yogyakarta's product, price, location, and promotion all affect sales. This study focused on customers who had previously visited the carpet shop AB07 Yogyakarta. A purposive sampling technique was utilized in this study to ensure that no population was sampled. In order to collect data for this study, a questionnaire (questionnaire) was used. In this study, descriptive analysis and statistical data are conducted with SPSS 23. This study found that the product marketing mix, price, location, and promotion all had an impact on sales simultaneously at the carpet shop AB07 Yogyakarta. Product, location, and promotion all have a significant impact on sales, while price has no significant effect. The R Square of 85% indicates that the marketing mix has a significant impact on sales. Keywords: Marketing mix; Sales.